INTERACTION BETWEEN RELIGION AND POLITICS UN WESTERN AND EASTERN EUROPE: THE COMMON AND THE DISTINCTIVE FEATURES - Tēraudkalns, Valdis (Via Latgalica, 2009)
The common and the distinctive features in the interaction between religion and politics in Western and Eastern Europe are discussed in the paper. At the beginning, the relative, flowing character of the concepts used is outlined, and the difficulties are indicated in making generalizations, since Europe sees great diversity regarding the involvement of religions in politics. The author also outlines the causes for greater interest of religious groups in politics – a large number of religious practitioners refuse to acquiesce with the place allocated for religion in the private space, where it was positioned by the Enlightenment. In the civil society, which strives to facilitate the participation of various society strata in the political process, the new tendency should not be perceived negatively. Full-value existence of democracy is inconceivable without the principles of solidarity and justice and public awareness of them, however, these are ethical categories. Increase of intolerance in many places of Europe makes one reflect upon the fact that the agreement of the public majority about the minimum common values is quite indispensable. However, in a secular state, religious groups cannot claim privileges and situation control. This is impossible also due to the fact that collisions of ideas are taking place also in religions and their movements themselves, and therefore, a discussion about the content and quality of politics is not to be perceived in a simplified way as a dialogue between the secular part of the society and the religious practitioners, but at the same time it is a conversation (often stressful) within the religious groups. The common features of the process of interaction between the Eastern and Western Europe: (1) increase of the role of religion in public space characteristic of post-secular society; (2) religion is a social phenomenon, therefore, unavoidably, the opinions and activities of its practitioners affect politics; (3) secularization, although on a different degree, affect all Member States of the European Union; (4) all the more actively, religious minorities announce themselves in public space. The different features: (1) in Eastern Europe, a larger number of people trust in churches than in Western Europe, which increases their role also among a large part of population who use to be secularly oriented on the daily routine; (2) the religious organizations in Eastern, more than in Western Europe, conceive spirituality as primarily directed towards maintaining definite ethical standards; (3) in Eastern Europe many religious organizations still are forming relations with the state and the public majority according to the principle of medieval Christendom, which provided special privileges for the church; (4) in Eastern, more than in Western Europe, the religious organizations are more sympathizing to the rightist forces. The religious groups, alongside with other non-governmental organizations, can provide an essential contribution in the discussions about the Western democratic models in the future, but they must be able to “translate” their ideas into rational arguments understandable to the secular society, avoiding theological naivety, which sees sacred texts as a monolith system of values to be transferred directly to the contemporary society.